2016
DOI: 10.1158/1535-7163.mct-15-0636
|View full text |Cite
|
Sign up to set email alerts
|

Human Neural Stem Cells Overexpressing a Carboxylesterase Inhibit Bladder Tumor Growth

Abstract: Bladder cancer is a significant clinical and economic problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[22] Thes pectroscopic date for the synthetic (À)-farnesiferol C( 1)w as identical to the published valueso ft he natural product, and the optical rotation for the synthetic (À)-farnesiferol C( 1)w as in good agreement with the reported value for the natural product. [17,23] In conclusion, ag old-catalyzed cycloisomerization of alkynediols for the diastereoselective synthesis of structurally diverse oxabicyclo[2.2.1]heptane scaffolds has been achieved. This chemistry was applied to the asymmetric total synthesiso ff arnesiferol C. DFT calculations were also consistent with the experimental observation.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…[22] Thes pectroscopic date for the synthetic (À)-farnesiferol C( 1)w as identical to the published valueso ft he natural product, and the optical rotation for the synthetic (À)-farnesiferol C( 1)w as in good agreement with the reported value for the natural product. [17,23] In conclusion, ag old-catalyzed cycloisomerization of alkynediols for the diastereoselective synthesis of structurally diverse oxabicyclo[2.2.1]heptane scaffolds has been achieved. This chemistry was applied to the asymmetric total synthesiso ff arnesiferol C. DFT calculations were also consistent with the experimental observation.…”
mentioning
confidence: 93%
“…[21] Recents tudies indicated that farnesiferol Ce xhibited antiviralactivitiesagainst HRV, [22] as wella sa ntiangiogenic activity. [23] Our synthesis commenced with the coupling of the ketone 13h with but-3-en-1-yllithium derivedf rom 4-bromobut-1-ene,a nd the resultant tertiary alcohol 14 was then subjected to dehydration by treatment with Burgess reagent to affordt he diene 15 in 63% yield for two steps (Scheme 1). Subsequent Wacker oxidation of the terminal olefin in 15 was conducted by the reactiono f15 with PdCl 2 and CuCl in the presenceo f oxygeni namixed solvent of DMF and H 2 Ot og ive the ketone 16 in 80% yield.…”
mentioning
confidence: 99%